2021
DOI: 10.3389/fimmu.2021.661761
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Is Overexpressed in Explant Lung Tissue and Broncho-Alveolar Lavage in Transplant-Related Pulmonary Fibrosis

Abstract: BackgroundConnective tissue growth factor (CTGF) is an important mediator in several fibrotic diseases, including lung fibrosis. We investigated CTGF-expression in chronic lung allograft dysfunction (CLAD) and pulmonary graft-versus-host disease (GVHD).Materials and MethodsCTGF expression was assessed by quantitative real-time polymerase chain reaction (qPCR) and immunohistochemistry in end-stage CLAD explant lung tissue (bronchiolitis obliterans syndrome (BOS), n=20; restrictive allograft syndrome (RAS), n=20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…The roles of CTGF/CCN2 in a variety of fibrotic disorders should be highlighted, as previous studies have reported that it is a pro-fibrotic factor, biomarker, and potential target (25)(26)(27). In carbon tetrachloride-induced liver fibrosis and congenital hepatic fibrosis, CTGF has been shown to be essential for fibrogenesis and could be a new therapeutic target for blocking the progression (28,29).…”
Section: Interference With Ctgf Detained the Development Of Pf In Vivomentioning
confidence: 98%
“…The roles of CTGF/CCN2 in a variety of fibrotic disorders should be highlighted, as previous studies have reported that it is a pro-fibrotic factor, biomarker, and potential target (25)(26)(27). In carbon tetrachloride-induced liver fibrosis and congenital hepatic fibrosis, CTGF has been shown to be essential for fibrogenesis and could be a new therapeutic target for blocking the progression (28,29).…”
Section: Interference With Ctgf Detained the Development Of Pf In Vivomentioning
confidence: 98%
“…It is characterized by variations in temporospatial heterogeneity fibrosis, the accumulation of fibroblasts (fibroblast foci), and subpleural and paraseptal honeycombing [ 42 ]. Vanstapel et al showed high expression of CTGF in fibrotic regions of restrictive allograft syndrome (RAS) lungs [ 43 ]. Furthermore, CTGF was found to be upregulated in cultured fibroblasts [ 44 ], injured epithelial cells [ 45 ], bronchoalveolar lavage and lung tissue [ 43 ], and plasma [ 46 ].…”
Section: Ctgf Maintains the Pro-fibrotic Environment In Ipfmentioning
confidence: 99%
“…Vanstapel et al showed high expression of CTGF in fibrotic regions of restrictive allograft syndrome (RAS) lungs [ 43 ]. Furthermore, CTGF was found to be upregulated in cultured fibroblasts [ 44 ], injured epithelial cells [ 45 ], bronchoalveolar lavage and lung tissue [ 43 ], and plasma [ 46 ]. CTGF is upregulated in patients with IPF as well as in pro-fibrotic mediators and pro-fibrotic environments that contribute to fibrogenesis [ 47 ].…”
Section: Ctgf Maintains the Pro-fibrotic Environment In Ipfmentioning
confidence: 99%
“…A recent study demonstrated higher levels of tissue CTGF expression in BOS and RAS compared to controls. Interestingly, BAL levels of CTGF were higher in RAS compared to BOS and stable patients, and also elevated at 3 months post-transplant in future RAS patients, perhaps suggesting a more specific role for CTGF in the pathogenesis of RAS [ 124 ].…”
Section: Repair and Regeneration Processesmentioning
confidence: 99%